Architecture and Key Technologies of Access Network for Satellite-Terrestrial Cooperation - Wei DENG; Lin ZHAO; Weiwen WENG; Qin DU; Ke MA; Jinxia CHENG; Long ZHANG (天地一体化信息网络)
With the development of ubiquitous and broadband communication requirements and the satellite-ground integration communication technology, the satellite and ground cellular communication industry ecosystem is gradually moving towards integration.In order to meet the application scenarios and technical requirements of satellite-terrestrial cooperation, the main technical challenges of the access network architecture were analyzed.Based on the overall principles of connection dynamics, unified resource management and controlled by ground network, the architecture of access network for satellite-terrestrial cooperation was elaborated from space segment, ground segment and cooperative segment.Key technologies of coverage cooperation, service cooperation, energy saving cooperation and capability cooperation were proposed based on the elaborated network architecture.By design cooperative network elements, such as intelligent dynamic cooperative unit, dynamic Xn interface, distributed TT＆amp;C units, the useful information between satellite and ground networks interacted deeply, a dynamic and efficient satellite-terrestrial cooperation mechanism could be realized.It could promote further complementarity between satellite and ground networks and improved overall system performance in resource utilization rate, energy consumption, and network construction cost.